GAME-BASED LEARNING PLATFORMS (Academicia Globe: Inderscience Research, 2023)
Today the educational paradigm is changing. Leading foreign universities are also increasingly introducing variative (hybrid form) educational trajectories, distance courses and teaching technologies. The impact of the COVID-19 pandemic has radically changed the traditional higher education landscape. The development of information and communication technologies ushered in a period of fundamental changes in human marriage. Modern technologies have brought a number of new approaches and views to the educational system, among all areas. This process requires continuous improvement of methods and resources in educational institutions. The improvement of the educational system, in particular, the organizational and legal mechanisms of distance education, is also among the top priorities for the development of digital infrastructure.